Countrymen (London : BBC Enterprises, 1990)
A year in the life portrait filmed against the magnificent backdrop of the English Lake District. This international award winning documentary series captures the totally diverse lifestyles of five men who live and work in a truly rural environment
Copy available in DVD format
Keywords: Country life in motion picture; Country life -- England